Managers' Attitude and Organizational Culture for Social Media Use in Supply Chain Efficiency and Responsiveness - Muhammed Kursad Ozlen (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - The research model proposes that (a) Managers' Attitude and Organizational Culture are fundamental in using Social Media for supply chain activities, and (b) Social Media Use increases Responsiveness and Operational Efficiency. Motivation - IT professionals are continuously improving advanced software programs for business activities to leverage their activities and benefits. Beside that there are Social Media platforms which provide online presence to the company and enhance communication of people. Literature has studies regarding the use of Social Media for supply chain activities which mainly focus on enhancing marketing and customer relationships and the integration of supply chains. However, there is scarcity of research from organizational and employee perspectives. Idea - This study aims to see the influence of Managers' attitude and Organizational culture for Social Media usage of supply chain professionals in their supply chain activities. Data - In order to test the relationships, a survey is conducted among 200 employees/professionals employed across 44 BiH SMEs which are parts of existing supply chains from various sectors. Tools - Descriptive statistics, confirmatory factor analysis-CFA and regression analysis are employed by using SPSS (version 20) software program. Findings - BiH companies have high operational efficiency and positive considerations about all model components. The results also show that the model works well in all dimensions. Contribution - This research serves as a good basis/template for similar future studies especially in BiH environment. Besides that, since there is few research from organizational and employee perspectives, this study purposes to see the impact of Managers' attitude and Organizational Culture for Social Media usage of supply chain professionals in their supply chain activities.
Keywords: L86; M11; 650; small and medium enterprises; social media use; operational responsiveness; operational efficiency; survey